2011
DOI: 10.5194/hessd-8-5769-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Use of ENVISAT ASAR Global Monitoring Mode to complement optical data in the mapping of rapid broad-scale flooding in Pakistan

Abstract: Envisat ASAR Global Monitoring Mode (GM) data are used to produce maps of the extent of the flooding in Pakistan which are made available to the rapid response effort within 24 h of acquisition. The high temporal frequency and independence of the data from cloud-free skies makes GM data a viable tool for mapping flood waters during those periods where optical satellite data is unavailable, which may be crucial to rapid response disaster planning, where thousands of lives are affected. Image differencing… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…In our experiments, using a single threshold resulted in missing water bodies in the far range, because there were no seeds captured: the threshold value excluded more pixels on open water in the far range, which usually has lower signal to noise ratios and higher calibration uncertainty. Work by O'Grady et al [21,46] also concluded that there are variations in the backscatter based on the incidence angle, given the varying noise levels of the scene. Another drawback of threshold-based methods for water mapping from SAR is that the threshold used for water mapping is severely affected by the noise (and noise floor) of the scene.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our experiments, using a single threshold resulted in missing water bodies in the far range, because there were no seeds captured: the threshold value excluded more pixels on open water in the far range, which usually has lower signal to noise ratios and higher calibration uncertainty. Work by O'Grady et al [21,46] also concluded that there are variations in the backscatter based on the incidence angle, given the varying noise levels of the scene. Another drawback of threshold-based methods for water mapping from SAR is that the threshold used for water mapping is severely affected by the noise (and noise floor) of the scene.…”
Section: Discussionmentioning
confidence: 99%
“…Thresholding techniques on SAR image for water mapping had been covered at length in the literature [4][5][6][7]20,21]. In its most simplistic form, thresholding consists of establishing a value below or equal to which pixel values are selected.…”
Section: Thresholdingmentioning
confidence: 99%
See 2 more Smart Citations
“…Mason et al (2010) mention the problem of misclassification due to topography, vegetation or canopy. O'Grady et al (2011) conclude that misclassification due to low backscatter values from non-flooded areas can be reduced via image differencing approaches. Matgen et al (2011) and Giustarini et al (2012) present a method relying on the calibration of a statistical distribution of "open water" backscatter values inferred from SAR images of floods.…”
Section: Relative Advantages Of Sar and Optical Imagingmentioning
confidence: 99%